Effect of Spraying Nitrogen and Some Plants Extracts in the Vegetative Growth on (Lavandula officinalis L) - Abbas, Alaulddin Abdulmunem (The Iraqi Journal of Veterinary Medicine, 2011)
This study was conducted in the special nursery in Mansour - Baghdad at 2011. to study the effect nitrogen 05 and 02 grams per liter in the form of urea as well as spraying four plant extracts which are Glycyrrhiz glabra uritica dioica Allium sativum Trigonella foenum – graecum and concentration of 5 grams per liter of distilled water and every extract plant in addition to the control treatment. Treatments were applied three times and the first was applied at 15-5-2011and the following applications were 15 days after the first application. Experiment were conducts using complete randomized block design with three replicates. Results, were analyzed using least significant differences at 5% probability. The results are summarized as follows:It was to spray the extract of Glycyrrhiza glabra significant effect in plant height it was 26.86 cm / plant compared to the treatment which was 2305 cm / plant, as well as to spray the extract of Uritica dioica significant effect in stem diameter of the main plant which was 0.34 cm with different insignificantly in compare with treatment of spraying extract of Trigonella foenum – graecum compared to the treatment was 0.21 cm also surpassed the treatment spraying 0.5 grams per liter of nitrogen significantly recipe in the number of branches per plant the number of branches 17.30 compared to the treatment comparison which reached 12.93.Either as the number of plant leaves it has surpassed the treatment spray Glycyrrhiza glabra extract significantly compared to other transaction it was 51083 leaf / plant compared to the treatment of non-spray amounting to 38783 leaf / plant and the results showed than spray treatment Glycyrrhiza glabra extract significantly in the description of total length of branches amounting to 395.90 cm / plant It also surpassed the treatment spray extract Uritica dioica significantly in the dry weight of leaves and was 61.13 gram / plant which was not different from the treatment of nitrogen 05 gram / L. As for the percentage content of chlorophyll pigment in the leaves was surpassed by 0.5 gN/L treatment of spraying nitrogen amounting to 33.60% which did